Optimal energy management of a residential-based hybrid renewable energy system using rule-based real-time control and 2D dynamic programming optimization method. (February 2020) - Jafari, Mohammad; Malekjamshidi, Zahra
Abstract: This paper presents a magnetically coupled hybrid renewable energy system (RES) for residential applications. The proposed system integrates the energies of a set of PV panels, a fuel cell stack, and a battery using a multi-winding magnetic link to supply a residential load. It can operate in multiple grid-connected and off-grid operation modes. An energy management unit including an off-line dynamic programming-based optimization stage and a real-time rule-based controller is designed to optimally control the power flow in the system according to the provided energy plan. The system is designed according to the required standards of the grid-connected residential RES. Different sections of the proposed system including steady-state operation, control techniques, energy management method and hardware design are studied in brief. A prototype of the proposed system is developed and experimentally tested for an energy management scenario considering both sunny and cloudy profiles of the PV generation. The energy distribution and cost analysis approved the benefits of the proposed system for residential consumers. Highlights: Combining dynamic programming based optimization and real-time control techniques. A multi-port multi-operation mode magnetically coupled renewable energy system. An optimized energy management technique using real-time and forecasted data. Design of residential renewable energy system according to the recent standards. Providing energy distribution and energy cost analysis of the system.